2001
DOI: 10.1086/324456
|View full text |Cite
|
Sign up to set email alerts
|

A Possible X-Ray Periodicity at Several Tens of Hours of an Ultraluminous Compact X-Ray Source in IC 342

Abstract: A long (155 hours) ASCA observation was performed of two ultra luminous compact X-ray sources, Source 1 and Source 2, in the spiral galaxy IC 342. While Source 1 that was in a hard spectral state varied little, Source 2 that was in its soft spectral state varied significantly on a time scale of about one day. The rms variation amplitude amounts to 5% in the 2-10 keV band, but is less than 4% in 0.7-2 keV. The variation involves statistically significant changes in the parameters describing multi-color disk bla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…The period is 27:0 AE 0:7 ks, and Bauer et al (2001) argue against the notion that this source is a foreground Galactic AM Her type system based primarily on the low surface density of Galactic X-ray sources in this direction (l ¼ 311 , b ¼ À3=8). Another IXO in IC 342 is possibly periodic, with a period of 31 or 41 hr, in agreement with that expected for a semidetached binary consisting of a black hole and a mainsequence star of tens of solar masses (Sugiho et al 2001).…”
Section: Introductionsupporting
confidence: 81%
“…The period is 27:0 AE 0:7 ks, and Bauer et al (2001) argue against the notion that this source is a foreground Galactic AM Her type system based primarily on the low surface density of Galactic X-ray sources in this direction (l ¼ 311 , b ¼ À3=8). Another IXO in IC 342 is possibly periodic, with a period of 31 or 41 hr, in agreement with that expected for a semidetached binary consisting of a black hole and a mainsequence star of tens of solar masses (Sugiho et al 2001).…”
Section: Introductionsupporting
confidence: 81%
“…For the source Circinus CGX-1, Bauer et al (2001) claim periodic variations of 7.5 hours, and argue against it being a foreground galactic binary because of the absence of an optical counterpart to m v > 25.3 magnitudes, and on general statistical grounds. The other possibly periodic ULX is in the galaxy IC342 (Sugiho et al 2001) and has a suggested period of 31 hours or 41 hours, which is consistent with the orbital period of a semidetached binary with a BH and a main-sequence star of several tens of solar masses. Recently Terashima & Wilson (2003) reported a ULX in M51 with a > 50% variation separated by about two hours.…”
Section: Do Intermediate Mass Black Holes Exist?supporting
confidence: 63%
“…The second possibility is that the X-rays are beamed, and we happen to be in the beam, the right interpretation for many of these sources, according to Georganopoulos et al (2002). Beaming leads one to expect rapid variability, as is indeed the case for some, perhaps most, of them (Sugiho et al 2001;Strickland et al 2001).…”
Section: Intermediate Mass Black Holesmentioning
confidence: 99%